Analisis Kebijakan Inovasi Kurikulum Pendidikan untuk Mempersiapkan Generasi Penerus Indonesia Emas 2045 - Benhur Ismail; Nur Rosidah; Teguh Purwito; Ansori Dasa Putra; Sri Andayani (Lentera: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze the effectiveness and suitability of educational curriculum innovation policies in Indonesia in preparing the next generation for the Golden Indonesia 2045 Vision. Using a qualitative research method with a literature review approach, data were collected from various scientific literature and policy documents published between 2015-2025 via Google Scholar Labs. The analysis results indicate that curriculum transformation, particularly the Kurikulum Merdeka (Emancipated Curriculum) and the integration of deep learning approaches and artificial intelligence (AI), is conceptually aligned with the demands of 21st-century competencies (4C skills, digital literacy, and Pancasila character). However, field implementation still faces significant challenges, such as regional infrastructure disparity, teacher competency and adaptability readiness, and inconsistency in policy application. This study concludes that to achieve the Golden Indonesia 2045 target, a comprehensive evaluation, bottom-up capacity building for educators, equitable distribution of digital-based educational facilities, and holistic synergy among all stakeholders are required